Aktualisasi Nilai-nilai Pendidikan Islam Pluralis dalam Semboyan Ragem Sai Mangi Wawai Masyarakat Tulang Bawang Barat - Hayyu Mashvufah; Farida Ulvi Na’imah; Lukman Surya; Muhammad Rofiq Anwar (Bustanul Ulum Journal of Islamic Education, 2023)
Having varied ethnics, cultures, religions, or faiths, Indonesia is considered a multicultural nation in today’s world. The phenomenon of violence in the name of religion, ethnicity, and culture has shown that humans have failed to understand heterogeneity, diversity, and plurality. For responding that phenomenon, the goverment West Tulang Bawang regency was implemented Islamic pluralism education's concept based on the meaning of Ragem Sai Mangi Wawai symbol of Lampung Pepadun peoples. This research with ethnographic approach and qualitative descriptive method was focused on implementation of Islamic pluralism education in West Tulang Bawang regency. The findings showed that Tulang Bawang Barat regency has applied Islamic pluralism education based on Ragem Sai Mangi Wawai with a cultural-themed concept. Its was illustrated through several society activities, such as the 47th Musabawah Tilawatil Program (MTQ) Lampung province, the colloquium Center for the Study of Religious Moderation with Islamic religious instructors of West Tulang Bawang Barat regency, ceremony of culture begawi of Lampung Pepadun, and implementing education program based nenemo's culture of philosophy